A New Genus of Tetragnathid Spiders from Papua New Guinea (Aranei, Tetragnathidae) - Marusik Yuri; Omelko Mikhail (National Academy of Sciences of Ukraine, 2022)
Nediphya gen. n. and four new species, N. lehtineni sp. n. (type species), N. hippai sp. n., N. lyleae sp. n. and N. padillai sp. n. are described from Papua New Guinea. Some somatic characters of Nediphya gen. n. such as modified eyes and a prolateral row of stiff setae on legs I and II resemble those of Diphya Nicolet, 1849, but the morphology of its copulatory organs indicates it belongs to Nanometinae, a subfamily known only from Australasia. Th e status and composition of Nanometinae are briefly discussed. Nanometa gentilis Simon 1908 (the type species of Nanometa Simon, 1908), thought to be known only from the female, was actually described from both sexes.